Pengaruh PDRB, upah minimum, jumlah penduduk terhadap pengangguran kabupaten/kota provinsi Jawa Tengah tahun 2019-2023 - Nanda Aji Setyaputri; Wiwik Nurfiana; Arfina Nur Insani; Dyah Maya Nihaya; Ita Nuryana (Universitas Negeri Surabaya, 2025)
This study aims to determine the effect of Gross Regional Domestic Product (GRDP), Minimum Wage and Total Population variables on the variable Unemployment Rate in Central Java Province in 2019-2023. The analysis tool uses the E-views 13 program with a regression model through panel data. Hypothesis testing through F test, T test and coefficient of determination R2. The results showed that the variables of GRDP and Minimum Wage had no significant effect on the Unemployment Rate in Central Java Province in 2019-2023. Meanwhile, the Total Population variable has a significant effect on the Unemployment Rate in Central Java Province in 2019-2023.